2017
DOI: 10.2478/prilozi-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Surgical Margin State in Patients Undergoing Cold Knife Conization – A Single Center Experience

Abstract: In the current study, we have found no association between the inherent characteristics of the patient and the surgeon and the surgical margin state after a CKC. The most important predictors for positive margins were the severity of the lesion and the cone depth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(30 reference statements)
1
0
0
Order By: Relevance
“…In addition, MI was significantly lower in GI-1 than in GI-2 (44.1% vs. 67.2%, p = 0.03). These results correlate with those of previous studies that demonstrated that deeper conization reduces MI [ 25 , 26 , 27 ]. Although MI can decrease with increasing depth of conization, deep conization is associated with adverse obstetric outcomes, postoperative bleeding and cervical stenosis [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, MI was significantly lower in GI-1 than in GI-2 (44.1% vs. 67.2%, p = 0.03). These results correlate with those of previous studies that demonstrated that deeper conization reduces MI [ 25 , 26 , 27 ]. Although MI can decrease with increasing depth of conization, deep conization is associated with adverse obstetric outcomes, postoperative bleeding and cervical stenosis [ 28 ].…”
Section: Discussionsupporting
confidence: 92%